Analysis of the Effect of Debt-to-Equity Ratio, Profitability, and Firm Size on Dividend Payout Ratio with Effective Tax Ratio as an Intervening Variable - Indarto Indarto; Dian Indudewi; Naratama Hermawan (Journal of Creative Power and Ambition (JCPA), 2026)
The phenomenon of dividend puzzle and the inconsistency of results (research gap) from previous studies are the background to this study. This study aims to analyze the effect of Debt to Equity Ratio (DER), Profitability (ROA), and Firm Size on Dividend Payout Ratio (DPR) with Effective Tax Ratio (ETR) as an intervening variable. The research method used is quantitative with an empirical study of companies listed in the LQ45 index on the Indonesia Stock Exchange for the period 2022–2024. The data analysis techniques applied panel data regression analysis with the Fixed Effect Model (FEM) estimated using Robust Standard Errors (PCSE). The results of the study indicate that company size has a negative and significant effect on ETR, ETR is proven to have a negative and significant effect on dividend policy, which means the lower the effective tax burden, the higher the dividends distributed; Company size is the most dominant determinant that has a positive effect on dividend policy; DER and profitability (ROA) are not found to have a significant effect on dividend policy directly in this sample. Regarding the mediation role, ETR is proven to mediate the effect of company size on dividend policy significantly, but is not proven to mediate the effect of DER and profitability on DPR.